Laboratory evaluation of the efficacy of the juvenile hormone analog fenoxycarb for controlling the eastern spruce budworm, Choristoneura fumiferana (Clemens) (Lepidoptera: Tortricidae) - Hicks, Barry J., 1964- (1992)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1993. Biology Bibliography: leaves 68-80. In process